Scaffold-Free Strategies in Dental Pulp/Dentine Tissue Engineering: Current Status and Implications for Regenerative Biological Processes - Mohammad Samiei; Martin Conrad Harmsen; Elaheh Dalir Abdolahinia; Jaleh Barar; Xenos Petridis (Bioengineering)
Conventionally, root canal treatment is performed when the dental pulp is severely damaged or lost due to dental trauma or bacterial endodontic infections. This treatment involves removing the compromised or infected pulp tissue, disinfecting the root canal system, and sealing it with inert, non-degradable materials. However, contemporary endodontic treatment has shifted from merely obturating the root canal system with inert materials to guiding endodontic tissue regeneration through biological approaches. The ultimate goal of regenerative endodontics is to restore dental pulp tissue with structural organization and functional characteristics akin to the native pulp, leveraging advancements in tissue engineering and biomaterial sciences. Dental pulp tissue engineering commonly employs scaffold-based strategies, utilizing biomaterials as initial platforms for cell and growth factor delivery, which subsequently act as scaffolds for cell proliferation, differentiation and maturation. However, cells possess an intrinsic capacity for self-organization into spheroids and can generate their own extracellular matrix, eliminating the need for external scaffolds. This self-assembling property presents a promising alternative for scaffold-free dental pulp engineering, addressing limitations associated with biomaterial-based approaches. This review provides a comprehensive overview of cell-based, self-assembling and scaffold-free approaches in dental pulp tissue engineering, highlighting their potential advantages and challenges in advancing regenerative endodontics.